BMA new guide to medicine & drugs - O'Shaughnessy, Kevin M.
A complete home reference to prescribed and over-the-counter medication.Discover how medicines work, what they treat, their risks, benefits, and side effects from this new edition. Clear and easy-to-use, the BMA New Guide to Medicines and Drugs explains what the major drug groups are and what they are used for. It explains how drugs work, dosage and side-effects, and possible interactions with other medicines. Clear, concise, and jargon-free, this book provides guidance for anybody taking medication or wanting to know more about the drugs used in common medical practice